Location Choice and Employment Decisions: A Comparison of German and Swedish Multinationals - Sascha O. Becker; Karolina Ekholm; Robert Jäckle; Marc-Andreas Muendler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
Using data on German and Swedish multinational enterprises (MNEs), this paper analyzes determinants ofinternational location choice and the degree of substitutability of labor across locations. Countries with highly skilled labor forces strongly attract German but not necessarily Swedish MNEs. In MNEs fromeither country, affiliate employment tends to substitute for employment at the parent firm. At the margin, substitutability is the strongest with respect to affiliate employment in Western Europe. A one percentlarger wage gap between Germany and locations in Central and Eastern Europe (CEE) is associated with 900 fewer jobs at German parents and 5,000 more jobs at affiliates in CEE. A one percent larger wage gap between Sweden and CEE is associated with 140 fewer jobs at Swedish parents and 260 more jobs at affiliates in CEE.
Keywords: F21; F23; J21; J23; 330; Multinational enterprises; location choice; multinomial choice; labor demand; translog cost function